HUBUNGAN REGULASI DIRI DALAM BELAJAR DENGAN PROKRASTINASI AKADEMIK PADA MAHASISWA PROGRAM STUDI ILMU KEPERAWATAN UNIVERSITAS MUHAMMADIYAH GORONTALO - Salahudin Liputo; Ismail Utina (Elsia: Jurnal Psikologi Manusia, 2023)
This research was conducted at the Muhammadiyah University of Gorontalo. The purpose of this study was to determine the relationship of self-regulation in learning with Academic Procrastination of Nursing Science students. The research method used in this study is a quantitative correlational research method of rank spearmen. The sample in this study amounted to 63 people. The sampling method is purposive sampling. In this study, it shows that self-regulation in nursing students' learning is mostly in the moderate category, namely 49 people 77.8%. while academic procrastination is also in the moderate category with 45 people 71.4%. It can be concluded that the data analysis between the variables of self-regulation in learning and academic procrastination in nursing students has a correlation coefficient of r = -0.545 with p = 0.000. These results indicate that there is a  negative relationship between self-regulation in learning and academic procrastination. The higher the self-regulation in learning, the lower the academic procrastination of nursing students.